Aural Cultures - Walter Phillips Gallery, Banff (Banff Toronto : Walter Phillips Gallery - The Banff Centre for the Arts Banff YYZ Books Toronto, 2004)
Sounds resonate in nearly every social activity - from symphonic concerts and ritual chants to cacophonous revelries and respectful silences. These acoustic situations do more than reflect cultural sensibility, they create it as a living presence. Aural Cultures is a timely and comprehensive collection of essays and artists' projects that examines sound in art and contemporary culture. The authors come from diverse fields, including sound construction, communication, performance, anthropology, art history, cinema studies, literature and philosophy. A CD of sound art recordings by renowned international and Canadian artists accompanies the publication.
Bean, Robert ; Birkbeck, Eimer ; Dyment, Dave ; Gervais, Raymond ; Hamilton, Ann ; Hiller, Susan ; Kaye, Lewis ; Kersels, Martin ; Kim, Soo-Ja ; Komar & Melamid ; Marclay, Christian ; McCartney, Andra ; Neshat, Shirin ; Olson, Daniel ; Savoie, Claire ; Sierra, Santiago ; Simmons, Don ; Su-Mei Tse
Notes on contributors (auteurs) p. 280-285
Engels
Catalogue of the exhibition "Aural Cultures" at the Walter Phillips Gallery in Banff, 23.04.2005 - 12.06.2005
boek